Rotational and translational dynamics of anisotropic granular particles. (29th August 2018) - Sánchez, Rodrigo; Díaz-Leyva, Pedro
Abstract: A system of asymmetric, elongated granular particles is studied experimentally. The translational and rotational dynamics are examined via their velocity distributions. We find the dynamics of this system is governed by clustering, which at least for dynamical purposes must be understood differently for translational and for rotational motion, and is quantified via a dimensionless parameter.